Survey of Pharmacopuncture Education in Korean Traditional Medicine Schools - Byung Woo, Kim; Chung San, Lim; Ga Young, Choi; Dae In, Kang; Hee Choon, Lee; Hyun Do, Kim; Ki Rok, Kwon (Korean Pharmacopuncture Institute, 2010)
Objectives: This investigation was conducted to evaluate current education status of pharmacopuncture in Korean traditional medicine schools and suggest improvement in the structure of pharmacopuncture education. Methods: Among the eleven Korean traditional medicine schools in the country, six schools participated in the survey. 252 students in fifth and sixth year whom have finished pharmacopuncture studies completed were given questionnaire developed for the purpose and survey results were analyzed. Results : 1. For the question pertaining to the text used for the pharmacopuncture lecture, a significant difference was witnessed suggesting that few schools were not utilizing common textbooks. 2. For the item pertaining to the lecture progression, each school showed significant difference and student satisfaction rate differed vastly between schools. 3. Lecture hours and lecture materials were also significantly different between schools and overall satisfaction rate was low. 4. All of students participated in the survey had high expectation in the clinical applications of pharmacopuncture treatment. Conclusions: Above findings indicate that students at Korean traditional medicine schools throughout the nation have high expectation for pharmacopuncture, but lack of standardized education system and materials and qualified instructors calls for immediate modification in the education of pharmacopuncture studies.